(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Financial institutions are a crucial part of an effective financial system, which is a must for everynation’s economic progress. The growth of our economy is largely dependent on rural and agriculturalprogress because a large portion of the Indian population lives in rural areas. This progress isdependent on a number of factors, including entrepreneurship, transportation and communicationinfrastructure, effective production methods, skilled management techniques, and, most importantly,timely and adequate financial resources. The significance of financial institutions in this setting cannotbe overstated. These financial institutions play a crucial role in the rural and agriculture development ofthe nation by promoting entrepreneurship, enhancing the financial resources available to small andcottage industries, and meeting the long- and medium-term financial requirements of the agricultural aswell as industrial sectors.